BUSINESS MODELS BASED ON SUSTAINABILITY. PRACTICAL EXAMPLES - Agata RUDNICKA (Modern Management Review, 2016)
Modern companies which look for sources of competitive advantage are more and more often taking into consideration concepts that allow them to assess their business activities in wider perspective than only of financial or marketing nature. The concept of sustainable development has become an important element in the public debate on the role and place of business in the modern society. Business organizations are expected to behave in socially responsible way including economic, ecological and social aspects of their operations. Sustainability, next to the other concepts, helps to understand complex relationships and improves ways of gaining common goals in a win-win strategy.